Fucoidan changes lipid accumulation in the liver of common carp (Cyprinus carpio) by modulating lipid and glucose metabolism - Li, Fang; Sun, Hanchang; Mei, Jianxi; Deng, Yaxin; Hu, Guangdi; Zhu, Chengke; Xiang, Xiao (Frontiers in Marine Science, 2024)
An 8-week feeding trial was conducted to investigate the effects of dietary fucoidan levels (0 mg/kg, 500 mg/kg, 1,000 mg/kg, 1,500 mg/kg, and 2,000 mg/kg) on the hepatic ultrastructure and the transcriptomic landscape within the liver tissue of common carp. The results revealed that the addition of 1,000 mg/kg fucoidan to the diet significantly altered the ultrastructure of hepatocytes. Notably, the quantities of lipid droplets, autolysosomes, enlarged mitochondria, and endoplasmic reticulum were increased in the hepatocytes. The liver transcriptome analysis revealed that DEGs were notably abundant in the 1,000-mg/kg fucoidan group in glucolipid metabolism signaling pathways, including eukaryotes and nicotinate and nicotinamide metabolism, steroid biosynthesis, and PPAR signaling pathways. The quantitative real-time PCR (qPCR) results showed an excellent agreement on those of RNA-seq for both up- and down-regulated genes (a total of 13 genes selected for validation). Furthermore, fucoidan significantly influenced hepatic glucolipid metabolism of common carp at the mRNA level. Notably, the inclusion of lower concentrations of fucoidan in the diet, specifically at 500 mg/kg and 1,000 mg/kg, was found to significantly enhance the expression of mRNA for genes involved in glycolysis, including hk, gk, and pk, as well as genes linked to lipogenesis, such as srebf1, fasn, elovl5, acsl3a, scd, fads2, and cyp24a1. Conversely, higher concentrations of dietary fucoidan, at 1,500 mg/kg and 2,000 mg/kg, were observed to markedly upregulate the mRNA expression of genes associated with gluconeogenesis, including pck1, pck2, gs, gsk3a, gsk3b, and g6pca.1, along with genes related to lipolysis, such as hadhb, acadl, ecil, acacba, cpt1, fabp1, and fabp3. In summary, varying levels of fucoidan intake appear to exert differential influences on the hepatic glucolipid metabolism of common carp, suggesting a complex dose-dependent regulatory mechanism. For the first time, this research has established that fucoidan possesses a pronounced regulatory influence on the hepatic glucolipid metabolism in fish. This discovery not only underscores its potential as an immunostimulant but also opens new avenues for its application as a feed additive, with implications for modulating the nutritional metabolism of aquatic species.